Pengaruh Edukasi Penanganan Luka Bakar bagi Relawan Melalui Media Sosial dan Gamifikasi - Munjiya Istiqamah; Novia Heriani; Diah Retno Wulan; Izma Daud (Tribhuwana Tunggadewi University, 2026)
Volunteer firefighters play an important role in providing initial burn injury management; however, they often face limitations in formal training. This study aimed to analyze the effect of social media- and gamification-based education on improving burn management literacy among volunteer firefighters. A pre-experimental study using a one-group pretest–posttest design was conducted involving 30 active Sanggalima volunteer firefighters as the study sample. The intervention was delivered over five consecutive days through educational posters shared via social media and reinforcement quizzes. Statistical analysis demonstrated a significant improvement in burn management literacy, with a significant difference between pretest and posttest scores (p = 0.001 0.05). It was concluded that social media and gamification-based education had a significant effect on improving burn management literacy among volunteer firefighters. This study recommends this educational model as an applicable and sustainable alternative strategy for relevant institutions to enhance volunteer firefighters' preparedness in providing appropriate initial burn care.